Фонтан «Дубовый» в Верхнем саду ГМЗ «Петергоф» – исторические метаморфозы - Чайникова, Олеся (Academia (Moscow, Russia), 2025)
Современные объекты культурного наследия за долгие годы своего существования неоднократно подвергаются реставрационным, ремонтным, восстановительным работам. Не всегда эти работы бывают достоверны и соответствуют первоначальному авторскому замыслу: облик фонтана, например, изменялся из-за применения недолговечных материалов скульптурного убранства. При этом применяли «подручные» материалы, не заботясь о соответствии общего архитектурного решения фонтана. Основу настоящей статьи составляют комплексные исследования с применением научного подхода при оценке результата деятельности по ремонтно-реставрационным работам пруда с фонтаном «Дубовый» в Верхнем саду ГМЗ «Петергоф» за 300-летний период его существования, что особенно актуально в условиях выполненной современной реставрации. В рамках исследования установлены исторические подходы, повлиявшие на облик фонтана, дошедшего до наших дней, а также послужившие основой для научного обоснования принятых решений в период современной реставрации. Modern cultural heritage sites have been repeatedly subjected to restoration, repair and renovation works over the long years of their existence. These works were not always reliable and corresponded to the original author's idea: the appearance of the fountain changed due to the use of short-lived materials for the sculptural decoration. At the same time, "improvised" materials were used, without caring about the compliance with the general architectural solution of the fountain. The basis of this article is a comprehensive study using a scientific approach to assess the results of the repair and restoration work of the pond with the Oak fountain in the Upper Garden of the Peterhof State Museum-Reserve over the 300-year period of its existence, which is especially relevant in the context of the modern restoration. The study established the historical approaches that influenced the appearance of the fountain that has survived to this day, and also served as the basis for the scientific substantiation of the decisions made during the modern restoration.